Stress-Induced Refractive Index Changes in Laser Fibers and Preforms - Pauli Kiiveri; Joona Koponen; Juha Harra; Ossi Kimmelma; Jijo Paul; Ville Aallos; Steffen Novotny; Hannu Husu; Heikki Ihalainen (IEEE Photonics Journal, 2019)
Refractive index profile of the core is a key design parameter in fiber lasers and amplifiers. During manufacturing, the initial information of the index profile is obtained from the preform, while ultimately the performance is defined by the index profile of the fiber. Depending on stresses and diffusion, the two profiles may be different. It is possible to predict more accurately the laser fiber refractive index when we apply a stress-induced index change model to the measured preform index profile data. The improved capability to predict the fiber index from preform increases the confidence in achieving the designed index profile in fiber, which enables faster process feedback and higher fiber yields.